ANALISIS FATWA DSN- MUI TERHADAP INOVASI PRODUK DI LEMBAGA KEUANGAN SYARIAH - Nafilah; Hayatun Nufus (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2025)
This study aims to analyze the role of the National Sharia Board of the Indonesian Ulema Council (DSN-MUI) in responding to Islamic financial product innovations through the issuance of fatwas. With the rapid development of the Islamic finance industry in Indonesia, adaptive sharia regulations for contemporary financial product innovations are needed. This research uses a descriptive qualitative method with a documentation study approach to DSN-MUI fatwas related to Islamic financial innovation products from 2010-2023. The results show that DSN-MUI has issued various fatwas regulating innovative products such as multi-service financing, Islamic credit cards, project-based Islamic bonds, and digital products such as Islamic electronic money. The DSN-MUI fatwa determination process uses istinbath methods including the Qur'an, hadith, ijma, qiyas, and the principles of fiqh mu'amalah. This study concludes that DSN-MUI fatwas play a significant role as a sharia legal basis for financial product innovation, maintaining sharia compliance, and providing legal certainty for Islamic financial institutions and customers. However, there are challenges in terms of response speed to rapidly developing product innovations and the need for more massive fatwa socialization to the public.